Assessment of quality and shelf life of goat liver stored at refrigerated temperature - T Yasmin; H Khatun; MA Hashem; MM Rahman; M Khan (Meat Research, 2022)
The objective of this study was to assess the quality and shelf life of goat liver storage at refrigerated temperature (4º C). For this purpose, raw goat liver samples were divided into five treatment groups in relevant of five days storage, treated as T1 (day 1or control), T2 (day 2), T3 (day 3), T4 (day 4) and T5 (day 5). Sensory attributes (color, flavor, juiciness and tenderness), proximate composition, pH value, cooking loss, biochemical properties such as free fatty acids (FFA), peroxide value (POV), thiobarbituricacid value (TBA), and microbial load such as total viable count (TVC), total coliform count (TCC) and total yeast mould count (TYMC) were carried out in each day of storage. The results show that color, flavor, juiciness, and tenderness were significantly decreased with increase the days of storage. Dry matter (DM) content significantly (p<0.05) increased, while crude protein, ether extract and ash contents were significantly (p<0.05) decreased with increase the days of storage. A significant (P<0.05) decrease of pH from 6.85 to 5.68 was observed during 5 days of storage. The percentage of cooking loss of 13.37 ml on day1 gradually increased to 33.84 mL on the fifth day of storage. In addition, the biochemical and microbial analysis also showed that FFA, POV, TBA, TVC, TCC and TYMC values were significantly (p<0.05) increased with increase the days of storage. Therefore, based on these results of shelf life evaluation, it may be concluded that goat liver will acceptable microbiologically and organoleptically up to the third day of storage at 4º C.